2020
DOI: 10.3390/vaccines8040633
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Cellular and Humoral Immunity against Foot-and-Mouth Disease Virus by Immunization with Virus-Like Particles Encapsulated in Monophosphoryl Lipid A and Liposomes

Abstract: Virus-like particles (VLPs) have emerged as promising vaccine candidates against foot-and-mouth disease (FMD). However, such vaccines provide a relatively low level of protection against FMD virus (FMDV) because of their poor immunogenicity. Therefore, it is necessary to design effective vaccine strategies that induce more potent immunogenicity. In order to investigate the means to improve FMD VLP vaccine (VLPFMDV) immunogenicity, we encapsulated VLPs (MPL/DDA-VLPFMDV) with cationic liposomes based on dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…IFN-γ plays a crucial role in this immune response by activating macrophages and natural killer (NK) cells to combat FMDV [31]. Research has shown that measuring the level of IFN-γ released by FMDV-specific T cells has the potential to replace the challenge test in assessing the effectiveness of FMD vaccines [32].…”
Section: Correlation Between the Quantity Of 146s And The Ifn-γ Secre...mentioning
confidence: 99%
“…IFN-γ plays a crucial role in this immune response by activating macrophages and natural killer (NK) cells to combat FMDV [31]. Research has shown that measuring the level of IFN-γ released by FMDV-specific T cells has the potential to replace the challenge test in assessing the effectiveness of FMD vaccines [32].…”
Section: Correlation Between the Quantity Of 146s And The Ifn-γ Secre...mentioning
confidence: 99%
“…There is no doubt that liposomal components of mycobacterial lipids can induce potent humoral and cellular immune responses to both mycobacterial and nonmycobacterial antigens 74 . The lipid extract of mycobacteria consists of various lipids separated by thin‐layer chromatography and immunostimulatory molecules.…”
Section: Liposomal Subunit Vaccines Against Tbmentioning
confidence: 99%
“…73 There is no doubt that liposomal components of mycobacterial lipids can induce potent humoral and cellular immune responses to both mycobacterial and nonmycobacterial antigens. 74 The lipid extract of mycobacteria consists of various lipids separated by thin-layer chromatography and immunostimulatory molecules. One advantage of using complicated instructions for vaccine administration is to activate many portions of the proinflammatory cascade, which leads to broader and longer-lasting biological activity.…”
Section: Liposomal Subunit Vaccines Against Tbmentioning
confidence: 99%
“…Both VLPs and OMVs have been studied for encapsulation and release from larger ordered structures, with the encapsulating agents in more recent years mainly being polymer-based ( Watkins et al, 2017a ; Jamaledin et al, 2020 ; Pastor et al, 2020 ; Gomes et al, 2021 ), and although liposomes have also been used ( Kim et al, 2020 ) ( Table 4 ).…”
Section: Hybrid Structuresmentioning
confidence: 99%